Prevalence of celiac disease among the Iranian population: A systematic review and meta-analysis of observational studies - Ahadi, Zeinab; Shafiee, Gita; Razmandeh, Rezvan; Keshtkar, Abbas- Ali; Sani, Mehri Najafi; Azemati, Bahar; Sanaei, Maryam; Heshmat, Ramin (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: The current systematic review and meta-analysis study assessed the prevalence of celiac disease (CD) in Iran. Materials and Methods: Electronic databases, including MEDLINE, SCOPUS, Web of Science, Cochrane library Collaboration, and Iranian scientific databases, were searched from 1993 to 2013 for English and Persian articles. The following terms were used, alone or combined, “celiac (MeSH),” “ceoliac,” “prevalence (MeSH),” and “Iran*.” Heterogeneity was assessed using the I2 statistic with a cut-off value of 50%, and the Chi-square test was used to define a statically significant degree of heterogeneity with a p value of <0.10. The publication bias of literatures was assessed by visual examination of the funnel plot and Begger’s funnel plot. Results: Meta-analysis was conducted on seven publications with 9,720 subjects. Overall, the pooled prevalence of CD among the Iranian population was 0.72% [95% confidence interval (CI): 0.62%–0.98%]. There was no significant heterogeneity among the studies (I2=4%, p=0.396). The pooled prevalence of CD on the basis of IgA-anti tissue transglutaminase (tTGA) and tTGA and duodenal biopsy positivity was 0.83% (95% CI: 0.69%–1.14%) and 0.79% (95% CI: 0.66%–1.09%), respectively. No significant publication bias was observed using the funnel plot and Begger’s funnel plot. Conclusion: CD prevalence among the Iranian population was approximately similar to that of the American and European populations.